How does supervisor-focused procedural justice explain the effects of person-focused leadership? The moderating role of leader-referenced relational-self. Issue 3 (4th May 2018) - Li, Jie; Laurence, Gregory A.; Blume, Brian D.
ABSTRACT: This study examines how the supervisor-focused procedural justice (SPJ) mediates the effect of benevolent paternalistic leadership on supervisor-directed organizational citizenship behaviour (OCBS) across employees with different types of leader-referenced relational-self. We use leader identification and traditionality to operationalize the concept of leader-referenced relational-self. Significant three-way interaction effects in both the leadership-SPJ and the SPJ–OCBS relationships are found. The SPJ-mediated effect of benevolent paternalistic leadership on OCBS is significant among employees whose leader identification and traditionality range from average to high levels. The findings suggest that leader-referenced relational-self is more complex than leader identification. Limitations, the implications for theory, research, and practice are discussed.